Macrophomina phaseolina on the tropical cover crops Mucuna pruriens var. utilis - Berner, D.K.; Killani, A.S.; Aigbokhan, E.I.; Couper, D.C. (1992)
During the rainy season of 1991, severely reduced plant stands and severely stunted plants were observed in several fields of the cover crop Mucuna pruriens (L.) DC. var. utilis (Wallich ex Wight) Baker ex Burck at the International Institute of Tropical Agriculture in Ibadan, Nigeria. Initial outbreak of symptoms followed a brief dry period, and subsequently more than 75% of the crop was lost. When the sites were replanted, the mucuna was again severely affected, although there was no dry period. Stunted plants had necrotic crowns and numerous necrotic lesions along the roots and runners. Only Macrophomina phaseolina (Tassi) Goidanich was consistently isolated from these lesions. Infestations of sterilized soil with a drench of a homogenized M. phaseolina culture, isolated from a symptomatic plant, resulted in poor seedling emergence in the screenhouse. Necrotic root symptoms were evident on emerged seedlings as well as on older mucuna plants taken from infested pots. M. phaseolina was reisolated and Koch's postulates proved. Tropical farm management increasingly relies on M. p. utilis as a rotational cover crop to restore fertility after cereal cultivation. This first report of the pathogenicity of M. phaseolina on mucuna indicates a potentially serious threat to this rotation.